PEMANFAATAN MINUMAN KEFIR SEBAGAI BAGIAN UPAYA PREVENTIF TERHADAP INFEKSI PNEUMONIA - Muhammad Luthfi Adnan (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2020)
Introduction: Pneumonia is an acute infection of the lungs and can be caused by bacteria, viruses, fungi, chemical exposure or the influence of other infections. Pneumonia is one of the diseases that cause the most deaths in the world after diarrhoea. Pneumonia caused by several microorganisms includes Haemophilus influenza type B (HiB), Streptococcus pneumonia, influenza virus and respiratory syncytial virus (RSV). The use of antibiotics is now one of the important treatments for the management of pneumonia. However, with the challenge of antimicrobial resistance, therapy is needed to eradicate pathogens and prevent resistance. One probiotic drink that has potential in the treatment of pneumonia is kefir. The development of science now shows the potential of kefir probiotic drinks to prevent pneumonia infection. Discussion: This literature study proves that probiotic drinks have an antibacterial effect to prevent pneumonia infection. The complex content of probiotic bacteria between specific lactic acid bacteria, acetic acid-producing bacteria and lactose and non-lactose fermenting bacteria that symbiotic with each other stimulates the immune system to be used for pathogens of pneumonia infection. The component of probiotic bacteria in kefir can reduce the level of antibiotic and antimicrobial consumption which can complicate the treatment of pneumonia infections. Conclusion: Probiotic drinks from kefir which have a high content of probiotic bacteria can reduce the risk of pneumonia infection